Functional inhibition or genetic deletion of acid sphingomyelinase bacteriostatically inhibits Anaplasma phagocytophilum infection in vivo. Issue 1 (21st November 2020) - Naimi, Waheeda A; Gumpf, Jacob J; Cockburn, Chelsea L; Camus, Sarah; Chalfant, Charles E; Li, Pin-Lan; Carlyon, Jason A
ABSTRACT: Anaplasma phagocytophilum infects neutrophils to cause granulocytic anaplasmosis. It poorly infects mice deficient in acid sphingomyelinase (ASM), a lysosomal enzyme critical for cholesterol efflux, and wild-type mice treated with desipramine that functionally inhibits ASM. Whether inhibition or genetic deletion of ASM is bacteriostatic or bactericidal for A. phagocytophilum and desipramine's ability to lower pathogen burden requires a competent immune system were unknown. Anaplasma phagocytophilum -infected severe combined immunodeficiency disorder (SCID) mice were administered desipramine or PBS, followed by the transfer of blood to naïve wild-type mice. Next, infected wild-type mice were given desipramine or PBS followed by transfer of blood to naïve SCID mice. Finally, wild-type or ASM-deficient mice were infected and blood transferred to naïve SCID mice. The percentage of infected neutrophils was significantly reduced in all desipramine-treated or ASM-deficient mice and in all recipients of blood from these mice. Infection was markedly lower in ASM-deficient and desipramine-treated wild-type mice versus desipramine-treated SCID mice. Yet, infection was never ablated. Thus, ASM activity contributes to optimal A. phagocytophilum infection in vivo, pharmacologic inhibition or genetic deletion of ASM impairs infection in a bacteriostatic and reversible manner and A. phagocytophilum is capable of co-opting ASM-independent lipid sources. Abstract : Pharmacologic inhibition or genetic deletion of acid sphingomyelinase impairs Anaplasma phagocytophilum infection in vivo in a bacteriostatic and reversible manner.